The Further Explanation of Quantum Entanglement - Huang, Jun Steed; Huang, Jiamin Moran; Zou, Qing (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Albert Einstein discovered that, two particles originated from the same source, when thestate of one changes, that ofthe other will change at the same time, no matter how far they are apart from each other. This phenomenon violates the special theory of relativity that was originated by himself. Later on he extended special relativity to general relativity, hoping to solve this problem, but with little success. In this paper, we are trying to elaborate more about our space central view of the phenomenon, wethen relate it tomore broad understanding of social and culture stories such as crimerate cycle, meditation power, super nature spiritual stories from ancient tombs around the world. We name it Super Natural Relativity.